Research in economic history. Vol. 28 - Hanes, Christopher; Wolcott, Susan K.; Field, Alexander J. (Emerald, 2012)
Volume 28 contains articles on the economic history of Europe and the U.S. including "Air Conditioning, Migration and Climate-related Wage and Rent Differentials" by Jeff E. Biddle; "The Rail-Guided Vehicles Industry in Italy, 1861-1913: the Burden of the Evidence" by Carlo Ciccarelli and Stefano Fenoaltea; "English Banking and Payments before 1826" by John A. James; "Retail Trade by Federal Reserve District, 1919 to 1939: A Statistical History" by Haelim Park and Gary Richardson; and "The Great Fortunes of the Gilded Age and the Crisis of 1893" by Hugh Rockoff.
Keywords: Business & Economics -- Economic History.; Business & Economics -- Economics -- Theory.; Business & Economics -- Economics -- General.; Economic history.; Taxation.; Economics -- History.; elektronické knihy; electronic books